2009
DOI: 10.1111/j.1471-4159.2008.05864.x
|View full text |Cite
|
Sign up to set email alerts
|

The CREB/CRE transcriptional pathway: protection against oxidative stress‐mediated neuronal cell death

Abstract: Formation of reactive oxygen and nitrogen species is a precipitating event in an array of neuropathological conditions. In response to excessive reactive oxygen species (ROS) levels, transcriptionally dependent mechanisms drive the up‐regulation of ROS scavenging proteins which, in turn, limit the extent of brain damage. Here, we employed a transgenic approach in which cAMP‐response element binding protein (CREB)‐mediated transcription is repressed (via A‐CREB) to examine the contribution of the CREB/cAMP resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(101 citation statements)
references
References 66 publications
8
92
0
1
Order By: Relevance
“…Given that ERK activation of CREB induces the expression of a number of antioxidant genes, activation of this pathway may represent an adaptive mechanism to reduce oxidative damage (reviewed in [73]). This contention is supported by the observation that molecularly interfering with CREB increases seizure-induced cell death and production of reactive oxygen species, and blocked the neuroprotective effect of BDNF [74].…”
Section: The Erk1/2 Mitogen-activated Protein Kinase Pathwaysupporting
confidence: 65%
“…Given that ERK activation of CREB induces the expression of a number of antioxidant genes, activation of this pathway may represent an adaptive mechanism to reduce oxidative damage (reviewed in [73]). This contention is supported by the observation that molecularly interfering with CREB increases seizure-induced cell death and production of reactive oxygen species, and blocked the neuroprotective effect of BDNF [74].…”
Section: The Erk1/2 Mitogen-activated Protein Kinase Pathwaysupporting
confidence: 65%
“…Stress response kinases are activated in a Ca 2ϩ -independent manner (2,17,22,37). Therefore, we analyzed the phosphorylation of p38, stress-activated protein kinase/Jun amino-terminal kinase (SAPK/JNK), and their related transcription factors cyclic AMP response element-binding protein (CREB) and its activating transcription factor (ATF-1) in WT and Parp1 Ϫ/Ϫ cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additional studies showed that the increases of inflammatory cytokines and glucocorticoids caused by stress lead to a reduction of central astrocytes, causing a decreased capacity of the glutamate transporters in astrocytes to transport intracellular glutamate and thus increasing extrasynaptic glutamate [50,51] . Notably, the excitatory neurotoxicity caused by glutamate (mainly oxidative stress) can also lead to reduced BDNF expression, which is the core mechanism of the occurrence of depression [52,53] (Fig. 2).…”
Section: The Infl Ammatory Cytokine Hypothesis Of Depression and Relamentioning
confidence: 99%